Observation of J/ψp resonances consistent with pentaquark states in Λ0b→J/ψK-p decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Physical review letters, 2015)
Observations of exotic structures in the J/ψp channel, which we refer to as charmonium-pentaquark states, in Λ0b→J/ψK−p decays are presented. The data sample corresponds to an integrated luminosity of 3 fb−1 acquired with the LHCb detector from 7 and 8 TeV pp collisions. An amplitude analysis of the three-body final state reproduces the two-body mass and angular distributions. To obtain a satisfactory fit of the structures seen in the J/ψp mass spectrum, it is necessary to include two Breit-Wigner amplitudes that each describe a resonant state. The significance of each of these resonances is more than 9 standard deviations. One has a mass of 4380±8±29 MeV and a width of 205±18±86 MeV, while the second is narrower, with a mass of 4449.8±1.7±2.5 MeV and a width of 39±5±19 MeV. The preferred JP assignments are of opposite parity, with one state having spin 3/2 and the other 5/2.
Im Titel ist "0" hochgestellt, "b" ist tiefgestellt, "b" steht unter "0"
Im Titel ist "-" hochgestellt
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, O. Grünberg, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, A. Zhelezov [und 686 weitere]
Gesehen am 06.07.2021